Strengthening the psychological well-being of students with single parent through the role of religiosity, parenting, and conformity - Janti, Sita Ana; Rahmatullah, Azam Syukur; Widigdo, Muhammad Syifa Amin (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2023)
Childcare is essential, and parents must educate children during their development phase. Parental care provided by both the father and mother has an important role. This research aims to determine the influence of religiosity, parenting patterns, and conformity on the psychological well-being of students with single parents. This research is a field study with a quantitative approach. The research subjects were chosen by randomly sampling as many as 63 students from 5 Muhammadiyah high schools in Yogyakarta. Research data was obtained from the distribution of the Scales of Psychological Well-being (SPWB), The Centrality of Religious Scale (CRS), The Parenting Scale (PS), and The Comfort Scale (CS). Research data was analyzed using a simple regression approach. The research results show that religiosity, parenting style, and conformity are proven to influence the psychological well-being of students with single parents. The religiosity variable contributed an influence of 28%, parenting style 25.3%, and conformity 32.6%; in other words, the conformity variable had the most significant influence compared to the religiosity and parenting variables. This research implies that improving the psychological well-being of students who have single parents can be done by increasing the value of religiosity and good conformity and paying attention to students’ parenting patterns.